High-performance one-pack ambient cross-linking latex binders containing low-generation PAMAM dendrimers and ZnO nanoparticles - Machotová, Jana; Rückerová, Adéla; Boháčik, Peter; Puková, Kateřina; Kalendová, Andréa; Palarčík, Jiří (Springer, 2018)
This study focuses on ambient-temperature self-crosslinking acrylic latex coating compositions containing poly(amidoamine) (PAMAM) dendrimers and ZnO nanoparticles in the role of inter-particle cross-linking agents and flash rust inhibitors. Low-generation amine-terminated PAMAM dendrimers as aqueous solutions were added into latices containing diacetone acrylamide repeat units in their polymer structure. The incorporation of ZnO nanoparticles (without any surface treatment) was performed during the synthesis of a polymer dispersion carried out by the semi-continuous emulsion polymerization technique. The latex storage stability and coating performance with respect to zinc oxide and PAMAM presence were evaluated and compared with a conventional zinc oxide-free coating composition containing adipic acid dihydrazide as the cross-linking agent. It was found that the novel latices containing both PAMAM dendrimers and ZnO nanoparticles exhibited a long-term storage stability and provided crosslinked transparent coating films of high gloss, enhanced mechanical properties, solvent resistance and excellent water whitening resistance. Moreover, the latex compositions containing PAMAM dendrimers as the inter-particle cross-linkers were shown to provide flash rust resistance.
Vysoce odolná jednosložková latexová pojiva síťující při běžných podmínkách a obsahující PAMAM dendrimery nízké generace a ZnO nanočástice
Keywords: Self-crosslinking latex; PAMAM dendrimer; Water whitening; Flash rust; Zinc oxide; Nanoparticle; Samosíťující latex; PAMAM dendrimer; zbělení vodou; blesková koroze; oxid zinečnatý; nanočástice